2022
DOI: 10.1111/jiec.13298
|View full text |Cite
|
Sign up to set email alerts
|

Contributing to carbon peak: Estimating the causal impact of eco‐industrial parks on low‐carbon development in China

Abstract: Low‐carbon development is associated with eco‐industrial parks (EIPs), but whether a causal relationship exists is unknown. A growing body of evidence from environmental engineering studies suggests that EIPs reduce carbon emissions, but few economic studies have assessed the causality, channels, and heterogeneity of this relationship. This study uses the staggered difference‐in‐difference method to construct a quasi‐natural experiment to assess the impact of national‐level EIPs on low‐carbon development. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 127 publications
0
5
0
Order By: Relevance
“…In the contemporary setting of the strategic objective of achieving the “carbon peak and carbon neutrality” and the advent of the green development period, enterprises need to attain green transformation through technical innovation [1] . In their study, Hajhashem et al [9] noted that the time of realization of technological innovations is often uncertain, and the effective implementation of such innovations might result in substantial advancements in performance.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the contemporary setting of the strategic objective of achieving the “carbon peak and carbon neutrality” and the advent of the green development period, enterprises need to attain green transformation through technical innovation [1] . In their study, Hajhashem et al [9] noted that the time of realization of technological innovations is often uncertain, and the effective implementation of such innovations might result in substantial advancements in performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…“Accelerating R&D (Research and Development), promotion, application of advanced energy-saving and carbon emission reduction technologies, encourage green consumption, promote green and low-carbon ways of production and life.” is an important strategic deployment for China in the New Era [1] . It provides crucial guidance and fundamental principles for the transformation and upgrading of China's manufacturing enterprises.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with Nie's research, who revealed that EIPs help achieve low-carbon development in China. Additionally, the effects of EIPs have regional heterogeneity [64]. Its effect is in the range of −0.752 to −2.318.…”
Section: Nonlinear Did Modelmentioning
confidence: 99%
“…Wu and Gao (2022) and Wu et al (2023) probed into how NDEP policy affects green innovation and technological advancement through the difference-in-differences (DID) model [17,18]. Nie et al (2022) analyzed the relationship between NDEP and carbon emission, claiming that green innovation is significant in facilitating low-carbon development of cities [19]. The above studies have only examined the direct impact of NDEP from an economic or environmental perspective, and much of the attention has been focused on a single indicator.…”
Section: Introductionmentioning
confidence: 99%